Algumas causas e consequências da superpopulação canina e felina: acaso ou descaso? - Lima, Alfredo Feio da Maia [UNESP]; Luna, Stelio Pacca Loureiro [UNESP] (My University, 2012)
Living with pets brings several benefits to the human beings, however, the inappropriate creation of animals, lack of knowledge of the fundamentals of the guard associated with the low level of education and lack of legislation, modifies the dog and cat population growth, which directly affects the well being of both, the humans and animals and may increase the rates of disease transmission. This review aims to describe some causes and consequences of overpopulation of dogs and cats.

A convivência com animais de estimação traz benefícios aos seres humanos, no entanto, a criação inadequada de animais, o desconhecimento dos fundamentos sobre a guarda responsável, associados ao baixo grau de instrução e a escassez de legislação, alteram os padrões de crescimento populacional de cães e gatos, o que afeta diretamente o bem-estar de todos os envolvidos e possibilita o aumento nas taxas de transmissão de doenças. A presente revisão de literatura objetiva descrever algumas causas e consequências da superpopulação de cães e gatos.
Some causes and consequences of canine and feline overpopulation: chance or negligence?
Keywords: Population control; Cats; Dogs; Responsible ownership; Zoonosis; Controle populacional; Cães; Gatos; Guarda responsável; Zoonoses